2012
DOI: 10.1002/pam.21614
|View full text |Cite
|
Sign up to set email alerts
|

Three Strategies to Prevent Unintended Pregnancy

Abstract: This paper presents results from fiscal impact simulations of three national-level policies designed to prevent unintended pregnancy: A media campaign encouraging condom use, a pregnancy prevention program for at-risk youth, and an expansion in Medicaid family planning services. These simulations were performed using Fam-ilyScape, a recently developed agent-based simulation model of family formation. In some simulation specifications, policies' benefits are monetized by accounting for projected reductions in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…However, economic information often is needed more immediately to determine the potential benefits of investing in specific interventions (Lee and Aos 2011; O'Connell et al 2009; Pew Center on the States 2012). Long-term projection models of economic benefits can help meet this need (Kahn et al 2010; Lee et al 2012a; Thomas 2012). The reliability and validity of projected estimates are enhanced by strong research designs and high-quality models (Welsh and Farrington 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, economic information often is needed more immediately to determine the potential benefits of investing in specific interventions (Lee and Aos 2011; O'Connell et al 2009; Pew Center on the States 2012). Long-term projection models of economic benefits can help meet this need (Kahn et al 2010; Lee et al 2012a; Thomas 2012). The reliability and validity of projected estimates are enhanced by strong research designs and high-quality models (Welsh and Farrington 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because the simulated media campaign has the ability to reach a large number people relatively cheaply, it is found that its costs per pregnancy and birth averted are generally lower than are those of these other programs. See Thomas (2012) for more information on all three simulations.…”
Section: Resultsmentioning
confidence: 99%
“…These taxpayer-savings estimates account for government spending on pregnant women and on children up to age five; and they are adjusted to reflect the fact that some prevented pregnancies will simply be delayed whereas others will be averted altogether. See Thomas (2012) and Monea and Thomas (2011) for additional information on the way that these savings estimates were developed.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that, from a societal perspective, every dollar invested in the program resulted in a savings of $2.65 in medical and societal costs (in 1994 dollars, and $4.24 in 2015 dollars) that included earnings and public assistance. Thomas (2012) used a modeling-based approach to examine the cost-benefit of a hypothetical teenage pregnancy prevention program based on outcomes from five evidence-based teenage pregnancy prevention programs in the United States. He estimated that from the perspective of the government, every dollar invested in teenage pregnancy programs results in $2.46 savings (in 2008 dollars, and $2.71 in 2015 dollars) from pregnancy care, infant medical care, and public assistance for children through age 5 (Thomas, 2012).…”
Section: Previous Research On Cas-carrera Pregnancy Prevention Programsmentioning
confidence: 99%